Analysis of Fuel Injection Pressure Effect on Diesel Engine Combustion Opacity Value - Andi Firdaus Sudarma; Hadi Pranoto; Mardani A. Sera; Amiruddin Aziz (International Journal of Advanced Technology, 2020)
The use of diesel engines for vehicle applications has expanded for decades. However, it produces black smoke in the form of particulate matter contains fine and invisible particles during operation. The popular method for measuring the smoke opacity is by using a smoke meter for its simplicity and less costly. Fuel injection pressure is one of the parameters that affect the emission significantly, and the proper nozzle adjustment can reduce the density of exhaust gases and improve the engine performance. The purpose of this study is to determine the optimum fuel spray pressure that produces the lowest opacity value and analyse the effect of fuel spray pressure on the opacity value at a different engine speed. The present experiment uses the Hyundai D4BB engine, and the pressure variations were implemented on the injector nozzle at 125, 130, and 135 kg/cm2. The engine was also tested with various engine idle speed, i.e., 1000, 1500, 2000, and 2500 rpm. It has been found that the optimum distance of fuel spraying is 147.679 mm with injector nozzle pressure 130 kg/cm2, and the value of opacity is 9.51%.